La lectura crítica y su mediación desde la formación ciudadana (2020)
To help build a more critical reader in the context of civic and political education that surrounds us. We have come across our inquiries about civic culture and social pedagogy, and we frankly believe that it can be the conceptual reference that, as a kind of hinge, helps us to give a selfcritical look to the critical reading teacher; and, at the same time, it becomes the duty of citizenship training in sociocultural circumstances as complex as those experienced by the nation of Colombia for a long time. Methodology: The information that was collected through the instruments used is presented below (see at the end annexed documents A and B: Documentary Analysis Matrix and Checklist), taking into account the categories and subcategories present in the study. and the significant aspects to be observed. For this analysis and interpretation, the following process was carried out: at first, what was related to the study plans, activities developed in the respective category and subcategories, was applied in the Document Analysis Matrix: 1) critical reading (analysis of literal, inferential and critical aspects); 2) citizenship competencies; 3) relationship between critical reading and civic education; Y 4) development of critical thinking from citizenship skills. Conclusions: In general, it is possible to say that the hypotheses proposed in the research project were corroborated: since in a context in which reading and writing has been represented as something that is far beyond a decoded mechanical process and that is traversed Due to various political motives, it is unable to establish a clear place for these practices within its pedagogical proposal, at least with regard to the formulation of its pedagogical model and the curricular guidelines.